ANALISIS PEMASARAN GABAH DI KELURAHAN KASIPUTE KECAMATAN WAWOTOBI KABUPATEN KONAWE (Analysis of Grain Marketing in Kasipute Village, Wawotobi District, Konawe Regency) - Hardin Hardin; Syamsinar Syamsinar; Wa Embe (Jurnal Ilmiah Sosio Agribis, 2024)
Konawe Regency has great potential in developing agricultural commodities, especially paddy fields. One of the areas that has the potential for developing paddy fields in Konawe Regency is Kasipute Village, Wawotobi District. Paddy fields grow well throughout the Konawe area, with Wawotobi District as its production center. The results of observations in Kasipute Village show that paddy farmers generally sell their farming products in the form of grain. The purpose of this study was to describe the pattern or channel of paddy/rice marketing, analyze marketing margins and marketing efficiency. The sample in this study were paddy farmers and paddy/rice traders in Wawotobi Village. The data was analyzed quantitatively to determine the marketing margin using calculations, the marketing margin was taken as the difference in price at the trader level after being reduced by the purchase price at the farmer level. The results showed that in marketing channel I, the percentage of the price received by farmers from the price paid by sub-district collectors was 78.43%. in marketing channel II, the percentage of the price received by farmers from the price paid by retailers was 86.27%. From the two rice marketing channels in Wawotobi District. We can see that the most efficient marketing channel because the price portion received by respondent farmers in marketing channel II is 86.27% of the price paid by consumers.Keywords: Grain, Margin, Marketing Channels